THE EFFECT OF PRINCIPAL DISCIPLINE AND COMPENSATION ON TEACHER PERFORMANCE RESULTS IN MADRASAH - Nur Laila (MANAGERE : Indonesian Journal of Educational Management, 2022)
This study aims to determine the significant effect of principal discipline and compensation on the performance results of all MTs teachers in Teluk Pandan District. This type of research is quantitative and associated with a population of 123 teachers, and the research sample is 94 teachers. The data collection technique uses a questionnaire. Simple and multiple linear regression analyses then analyzed the data. The results showed that the effect of principal discipline and compensation on teacher performance was 54.9%, while other factors influenced the remaining 45.1%. So it can be concluded that the better the principal's leadership and compensation, the higher the teacher's performance results.